Opportunistic radio and licensed users coexistence in cellular networks - Pereira, A.
A scenario based on an UMTS TDD opportunistic cellular system that operates over UMTS FDD licensed cellular networks is considered. Therefore we develop a simulation tool that addresses the goal of analysis and assessment of UMTS TDD opportunistic radio system in a coexistence environment with UMTS FDD primary cellular networks. The communication presents the main features of the tool, discusses and proposes metrics to evaluate the multisystem coexistence, and presents illustrative simulation results. These show that with a reasonable UMTS TDD opportunistic radio transmission power and considering realistic propagation environments, a moderate number of available frequencies allow the deployment of UMTS TDD opportunistic radio networks with small blocking probabilities.